Airborne microplastics and SARS-CoV-2 in total suspended particles in the area surrounding the largest medical centre in Latin America. (1st January 2022) - Amato-Lourenço, Luís Fernando; de Souza Xavier Costa, Natália; Dantas, Kátia Cristina; dos Santos Galvão, Luciana; Moralles, Fernando Negri; Lombardi, Suzette Cleuza Ferreira Spina; Júnior, Alfredo Mendroni; Lindoso, José Angelo Lauletta; Ando, Rômulo Augusto; Lima, Felipe Gallego; Carvalho-Oliveira, Regiani; Mauad, Thais
Abstract: Microplastics (MPs) have been reported in the outdoor/indoor air of urban centres, raising health concerns due to the potential for human exposure. Since aerosols are considered one of the routes of Coronavirus disease 2019 (COVID-19) transmission and may bind to the surface of airborne MPs, we hypothesize that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) could be associated with the levels of MPs in the air. Our goal was to quantify the SARS-CoV-2 RNA and MPs present in the total suspended particles (TSP) collected in the area surrounding the largest medical centre in Latin America and to elucidate a possible association among weather variables, MPs, and SARS-CoV-2 in the air. TSP were sampled from three outdoor locations in the areas surrounding a medical centre. MPs were quantified and measured under a fluorescence microscope, and their polymeric composition was characterized by Fourier transform infrared (FT-IR) microspectroscopy coupled with attenuated total reflectance (ATR). The viral load of SARS-CoV-2 was quantified by an in-house real-time PCR assay. A generalized linear model (GzLM) was employed to evaluate the effect of the SARS-CoV-2 quantification on MPs and weather variables. TSP samples tested positive for SARS-CoV-2 in 22 out of 38 samples at the three sites. Polyester was the most frequent polymer (80%) found in the samples. The total amount of MPs was positively associated with the quantification of SARS-CoV-2 envelope genes and negatively associated with weather variables (temperature and relative humidity). Our findings show that SARS-CoV-2 aerosols may bind to TSP, such as MPs, and facilitate virus entry into the human body. Highlights: The SARS-CoV-2 RNA was detected in 22 out of 38 air samples. MPs were positively associated with the quantification of SARS-CoV-2 envelope genes. SARS-CoV-2 envelope genes were negatively associated with temperature. SARS-CoV-2 envelope genes were negatively associated with relative humidity. Polyester was the most frequent polymer (80%) found in the samples.